Political Communication in Sub-Saharan Africa, Volume I
XV, 229 p. 2 illus.
Keywords: This book is one of two volumes that examines the role of political communication, media and language in transforming politics, governance and democracy in southern Africa. Interdisciplinary in approach, this first volume assesses themes including participatory politics, mass media, digital censorship, and social media in Sub-Saharan politics. It also considers how politicians utilise language and the media to legitimate their authority, influence citizens’ behaviour, and the ways in which they vote. It will appeal to all those interested in governance, political communication, media studies and African politics. Isaac Mhute is Associate Professor in the Department of Language, Literature and Culture Studies, Midlands State University, Zimbabwe and Senior Research Associate in the Faculty of Humanities, University of Johannesburg, South Africa. Esther Mavengano is Lecturer in the Department of English and Media Studies, Great Zimbabwe University, Zimbabwe and a Research Fellow at Technische Universität Dresden, Germany. .